Teaching and cultivation of high-level talents in Traditional Chinese Medicine nursing science (浅谈中医护理骨干人才的带教) - FAN Yan (范艳); WANG Xuesong (王雪送); LIU Yanna (刘燕娜); YANG Yu (杨宇); JIA Tieying (贾铁英); HU Shirong (胡世荣) (中西医结合护理)
Cultivation of high-level talents in Traditional Chinese Medicine (TCM) nursing science is of great importance for the TCM nursing development. This paper summarized the experience in teaching and cultivation of high-level talents in TCM nursing science. Basics of teaching, plan-making strategies and tips for better implementation of teaching were discussed in order to provide reference for cultivation of high-level talents the promotion of TCM techniques. (中医护理骨干人才的培养对促进中医护理事业的发展有着至关重要的意义。本文主要总结了中医护理骨干人才带教的相关经验, 包括带教的基础、带教计划的制定以及带教实施阶段的一些技巧, 以期为中医护理人才培养及中医护理技术的推广提供依据。)